Nadwat al muhadarah : muwasim Hajj 1386 H. min 21 Dilqa'dah 1386 H. al muwafiq 2-3-1967 ila 24 Dilhijjah 1386 H. al muwafiq 4-4-1967 - Rabitah-al-Alam-al-Islamiy (Majalah Rabitah-al-Alam-al-Islamiy, 1967)
ws.c.1